1988
DOI: 10.1128/mcb.8.9.3872
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of transcription in vitro by a glucocorticoid response element is mediated by a trans-acting factor.

Abstract: In vitro experiments with cell extracts prepared from a mouse mammary epithelial cell line demonstrated that a cis-acting glucocorticoid response element (GRE) of the mouse mammary tumor virus represses transcription from its homologous promoter. Competition transcription experiments, in which a molar excess of a restriction fragment that contains the GRE is added to the cell-free assay, revealed that a nuclear factor mediates in trans the negative regulation of mammary tumor virus transcription in vitro. Gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Previous studies of regulatory functions of the MMTV LTR pointed to sequences in the Ϫ140-to-Ϫ160 area as having negative effects, mainly on the basal level of transcription (32,39,40). A report on an activity affecting the glucocorticoid stimulation in a particular rat hepatoma cell line showed a negative effect as well (56).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of regulatory functions of the MMTV LTR pointed to sequences in the Ϫ140-to-Ϫ160 area as having negative effects, mainly on the basal level of transcription (32,39,40). A report on an activity affecting the glucocorticoid stimulation in a particular rat hepatoma cell line showed a negative effect as well (56).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, negative regulation of the enhancer is also an important mechanism for the control of heavy-chain expression. Negative-enhancer regulation may be a general mechanism for tissue-specific expression as negativeregulatory elements also have been found that are associated with the insulin 1 gene enhancer (Laimins et al 1986;Nit et al 1986), the B-interferon gene enhancer {Goodbourn et al 1986), and viral enhancers in embryonic stem cells (Gorman et al 1985), and mouse mammary epithelial cells (Langer and Ostrowski 1988).…”
Section: Models For Enhancer Repressionmentioning
confidence: 99%
“…Nevertheless, mutations in the HRE appear to affect differentially the response to these diverse steroid hormones (Gowland & Buetti, 1989) (Langer & Ostrowski, 1988) (Fig. 1).…”
Section: Steroid Hormonesmentioning
confidence: 99%